ANALISIS PERAN STRUKTUR HUKUM DALAM PENGEMBANGAN SISTEM PIDANA DI INDONESIA BERDASARKAN TEORI FRIEDMAN - Hanoko, Aimee Reyhansa; Sumanto, Listyowati (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
This article discusses the role of legal structures in the development of the criminal justice system in Indonesia using Lawrence M. Friedman's legal system theory approach. The main focus of this study is on the elements of structure, namely institutions, authority, and human resource capacity in criminal justice institutions, such as the police, prosecutors, courts, and correctional institutions. Although criminal law reforms have been carried out through the enactment of the 2023 Criminal Code and other supporting regulations, the effectiveness of their implementation is still hampered by the unpreparedness of the legal structures that enforce them. This article uses a normative and descriptive type of legal research. Secondary data was analyzed qualitatively based on a literature study, reviewing legal documents, scientific journals, and relevant research results. Conclusions are drawn using deductive logic. The results of the study show an imbalance between progressive legal substance and the reality of a slow, fragmented legal bureaucracy that is often overloaded with cases. Weak legal structures prevent the optimal achievement of criminal justice objectives such as resocialization, restorative justice, and rehabilitation. Therefore, criminal law reform must be accompanied by legal institutional restructuring so that the criminal justice system can function effectively and fairlyKeywords: Criminal Justice System, Legal Development, Legal Reform